Pengaruh Styrofoam Bekas pada Campuran AC-WC Menggunakan Batu Sungai Teik Toraja Utara - Febrianto Paembonan; Alpius; Charles Kamba (Paulus Civil Engineering Journal, 2022)
Styrofoam is a material that has the same additive properties as asphalt, namely thermoplastic, and is a new binder Styrofoam as an added material, which has the aim of knowing the characteristics of the AC-WC mixture using Teik river aggregate with raw materials. The characteristics of the AC-WC mixture using used Styrofoam added through the Conventional Marshall test obtained the largest average VIM value at 1% = 4.21%, for the FLOW value the largest average value was obtained at 1% = 3.50 , for the VMA value the largest average value was obtained at 1% = 17.83, for the VFB value the largest average value was obtained at 5% = 80.87 and stability obtained the largest average value at 5% = 1559 , 48 has met the 2018 Highways Standard. The effect of adding used Styrofoam to the AC-WC mixture greatly affects the Flow, VIM, VMA, VFB and Stability values.